Anomalous Aortic Origin of a Coronary Artery: A Report From the Congenital Heart Surgeons Society Registry. (January 2014) - Poynter, Jeffrey A.; Williams, William G.; McIntyre, Susan; Brothers, Julie A.; Jacobs, Marshall L.; ,
Background: Anomalous aortic origin of a coronary artery (AAOCA) is a common congenital heart lesion that may be rarely associated with myocardial ischemia and sudden death in the young. Evidence-based criteria for managing young patients with AAOCA are lacking. The Congenital Heart Surgeons Society (CHSS) established a multicenter registry of patients with AAOCA aged ≤30 years to develop these criteria. Methods: All institutional members of the CHSS are eligible to enroll patients. Patients were enrolled retrospectively if diagnosis of AAOCA occurred between January 1, 1998, and January 20, 2009, and prospectively from January 20, 2009 forward. The first phase of analysis explored possible associations between demographics, symptoms, coronary anatomy, and management using correlation analysis and logistic regression. Results: As of June 2012, 198 patients were enrolled from CHSS member institutions (median age at diagnosis = 10.2 years; 64% male). Data were extracted from clinical records. Fifty-four percent were symptomatic at presentation (most commonly chest pain, N = 78). The AAOCA was diagnosed at autopsy in two patients who presented with sudden death (one with anomalous aortic origin of the left coronary artery [AAOLCA]; one with a single ostium above a commissure giving rise to both left and right coronary arteries). Imaging reports documented anomalous aortic origin of the right coronary artery (AAORCA) in 144 patients, AAOLCA in 51 patients, and AAOLCA/AAORCA in 1 patient. Surgery or autopsy without surgery was performed in 106 patients (71 AAORCA [67%]; 31 AAOLCA [29%]; and 4 AAORCA/AAOLCA [4%]) at a median age of 12.6 years. Overall, 52% of patients with AAORCA versus 67% with AAOLCA had surgery. Most surgical operative reports described an intramural segment of the coronary artery with anomalous origin. Surgery correlated with symptoms, older age, and presence of an intramural segment in the setting of AAOLCA. Conclusions: Management decisions, including surgical referral, are associated with patient symptoms and coronary morphology. Information derived from annual follow-up of surgically and nonsurgically managed patients enrolled in the registry will eventually form the basis for development of evidence-based protocols to address the spectrum of risk and inform clinical decision making in this heterogeneous population of young patients.